VOLUNTARY RISK MANAGEMENT DISCLOSURE DETERMINANTS AND ITS IMPLICATIONS ON COMPANY VALUE - Popon Rabia Adawia; Herlina Puspa Dewi; Irwan Rutlan Atmadiredja (JMB : Jurnal Manajemen dan Bisnis, 2021)
The aim of this research is to examine the effect of voluntary risk management disclosure and its implication to firm value. Independent variables used in this research are product diversification, geographical diversification, type of industry and company size. Intervening variable is voluntary risk management disclosure. While the dependent variable in this study is firm value measured using Tobin’s Q. This research used a sample of non financial companies listed on the Indonesia Stock Exchange (IDX) in 2017. The sampling method in this research is purposive sampling and acquired 418 companies that meet the criteria. Hypothesis testing using multiple regression analysis. The results of this research showed that the higher the level of product diversification, geographical diversification, type of industry and company size, the higher the voluntary risk management disclosure. Voluntary risk management disclosure has a positive influential on firm value, the wider the disclosure of corporate risk management, will increase the firm value, otherwise the less disclosure of corporate risk management, will decrease the firm value or the value are getting worse. Keywords:  Product diversification, geographical diversification, type of industry, company size, voluntary risk management disclosure, firm value